Actin-dependent vacuolar occupancy of the cell determines auxin-induced growth repression - Scheuring, David; Löfke, Christian; Krüger, Falco; Kittelmann, Maike; Eisa, Ahmed; Hughes, Louise; Smith, Richard S.; Hawes, Chris; Schumacher, Karin; Kleine-Vehn, Jürgen (Proceedings of the National Academy of Sciences of the United States of America, 2016)
The cytoskeleton is an early attribute of cellular life, and its main components are composed of conserved proteins. The actin cytoskeleton has a direct impact on the control of cell size in animal cells, but its mechanistic contribution to cellular growth in plants remains largely elusive. Here, we reveal a role of actin in regulating cell size in plants. The actin cytoskeleton shows proximity to vacuoles, and the phytohormone auxin not only controls the organization of actin filaments but also impacts vacuolar morphogenesis in an actin-dependent manner. Pharmacological and genetic interference with the actin-myosin system abolishes the effect of auxin on vacuoles and thus disrupts its negative influence on cellular growth. SEM-based 3D nanometer-resolution imaging of the vacuoles revealed that auxin controls the constriction and luminal size of the vacuole. We show that this actin-dependent mechanism controls the relative vacuolar occupancy of the cell, thus suggesting an unanticipated mechanism for cytosol homeostasis during cellular growth.
First published December 29, 2015
Gesehen am 13.05.2020